A Review of the Evidence on Attitudes, Perceived Impacts and Motivational Factors for European Member State Collaboration for Pricing and Reimbursement of Medicines: Time for the EEA Member States to Apply Their Experience and Expertise in Evidence-Based Decision Making to Their Current Pharmaceutical Policy Challenges - Vella Bonanno, Patricia; Cassar, Vincent; Godman, Brian (Frontiers in Pharmacology, 2021)
In 2018/2019 there were a number of initiatives for collaboration between Member States in the European Economic Area (EEA) and the European Commission published a Proposal for a Regulation on health technology assessment. In view of the perceived benefits from collaboration, the experiences and challenges of these collaborative initiatives and the possible implications of the proposed legislation, a study of the evidence on attitudes, perceived impacts and the motivational factors towards European Member State collaboration regarding the pricing and reimbursement of medicines was conducted. This study adopted an evidence–based management approach by Barends and Rousseau. The main findings showed that Member States differed in their motivation for collaboration for different pharmaceutical activities. Member States favoured voluntary co-operation for all activities of pricing and reimbursement except for relative effectiveness assessments where Member State authorities had divergent attitudes and prioritised activities related to the sustainability of their healthcare systems and access to medicines. Contrastingly pharmaceutical companies strongly favoured mandatory cooperation for evaluation. Member States motivation for collaboration was highly dependent on the purpose, political will, implementation climate and cultural factors. Currently, with the experiences of ongoing collaborations, following the progress of the discussion at Council, and with a number of initiatives for new pharmaceutical strategy and policy, it is proposed that Member States use their trust, expertise and knowledge of application of evidence-based decision making for pricing and reimbursement of medicines and apply it to decide the future model for Member State collaboration. The applicability of principles of evidence-based management to pharmaceutical policy can be used as a starting point.